Does Music Encourage Residents to Purchase Commercial Insurance? Evidence From China - Lifei Gao; Li Wang; Shouji Sun; Guojun Wang; Xuemeng Ding (SAGE Open, 2023)
Commercial insurance is an important risk management tool whose demand is affected by psychological factors. Music can promote consumption by evoking non-random emotional and behavioral responses in consumers . Using data from the China Comprehensive Social Survey, we examined the impact of music on commercial insurance purchase behavior using a probit model, an instrumental variable, propensity score matching, and other methods. The results indicate that music can significantly increase the probability of residents purchasing commercial medical insurance and endowment insurance by 2.569% and 1.869%, respectively. Regarding the mechanism, music encourages residents to purchase insurance by increasing their general cognition, risk cognition, insurance cognition, and ability to manage risk. Furthermore, an analysis of heterogeneity shows that music plays a greater role in promoting the aforementioned behavior of residents with lower levels of education, lower frequencies of social interaction, internet usage, an agricultural household registration, and of residents with jobs.